2014
DOI: 10.1002/mus.24261
|View full text |Cite
|
Sign up to set email alerts
|

Changes in sensory function and force production in adults with type II diabetes

Abstract: Some, not all, motor performance deficits in T2D are associated with sensory dysfunction. Mechanisms responsible for these changes in adult-onset T2D are described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
41
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 20 publications
(48 citation statements)
references
References 40 publications
(95 reference statements)
6
41
1
Order By: Relevance
“…In some cases, these health state markers accounted for the observed behavioural differences in diabetic patients; in others, they magnified the group differences between diabetics and controls. Consistent with previous literature, tactile dysfunction positively correlated with A 1c , suggesting that worsened glucose control is globally associated with worsened sensory function. Baseline cognitive function was indicated to be negatively correlated with blood pressure .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some cases, these health state markers accounted for the observed behavioural differences in diabetic patients; in others, they magnified the group differences between diabetics and controls. Consistent with previous literature, tactile dysfunction positively correlated with A 1c , suggesting that worsened glucose control is globally associated with worsened sensory function. Baseline cognitive function was indicated to be negatively correlated with blood pressure .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the cognitive complications of diabetes, sensorimotor functions of all four extremities are known to be impaired with Type 2 Diabetes . Specifically, poor tactile sensation and presence of diabetic peripheral neuropathy have been linked to poorer balance control and increased fall risk in patients with Type 2 Diabetes .…”
Section: Introductionmentioning
confidence: 99%
“…During testing, dynamometers were placed 16 inches anterior to the patient torso, 6 inches away from the midline of the body toward the dominant hand. The wrist orientation was such that the hand was in a neutral position during testing . For pinch testing, the P200 device was held vertically with the non‐dominant hand.…”
Section: Methodsmentioning
confidence: 99%
“…Recent evidence has suggested that fine motor function is impaired in patients who have type II diabetes (T2D), even though they do not notice such deficits. Recent studies have also indicated that adults with T2D exhibit subtle yet significant differences in hand function in kinetic evaluation but not in assessments with clinical evaluation tools . As all manual tasks are performed by application of force through the hands or fingers, evaluation of kinetics yields a wealth of information regarding fine motor disability .…”
mentioning
confidence: 99%
See 1 more Smart Citation